Representing Love: From Poetry to Martyrdom or Language and Transcendence in Kierkegaard's Works of Love - Pattison, George (KIERKEGAARDIANA, 2002)
Representing Love: From Poetry to Martyrdom or Language and Transcendence in Kierkegaard's Works of Love